Perceptions of coaching behaviour and its impact on managerial of university team sports performance / Ahmad Fikri Mohd Kassim, Ellail Ain Mohd Aznan and Nurul Syuhadah Abdul Halim - Mohd Kassim, Ahmad Fikri; Mohd Aznan, Ellail Ain; Abdul Halim, Nurul Syuhadah (Universiti Teknologi MARA, Perlis, 2020)
Sports coaches is an important factor that affect athletes’ learning and development. Sports coaches is required to create fulfilling instructions, strategies, social relationship, and psychosocial outcomes for athletes’ development. Managerial coaching is an essential element of management in human resource development to improve individual performance. Coaching behaviour has key elements to improve individual or team performance. Therefore, this research aimed to investigate the athlete’s perception of coaching behaviour in team sport athletes. One hundred and twenty athletes from three (3) team sports, i. Football (n=40), ii. Netball (n=40) and iii. Hockey (n=40) completed a questionnaire pack assessing the study variables. Results revealed that there were significant differences between all the three (3) team sports for physical training, positive rapport behaviour, and negative rapport behaviour. Results also indicated significant differences perceived “Physical Training” between genders, and “Positive rapport” between genders. The findings of this study suggest athletes’ perceptions of their coach’s behaviour influence by athletes’ predilection through types of sports and gender. Thus, athletes’ perceptions of their coach behaviour have important values for coach’s approaches and management on team sports performance.